KELUARGA SAKINAH DALAM PERSPEKTIF HADIS - Kamarudin (Musawa: Journal for Gender Studies, 2022)
Family or household is seen as a foundation for the establishment of a society. The Prophetic Hadith views it as a sturdy tie in religion and society. Marriage is one of the media to organize social order. To ebstalish a harmonious family based on the principles of mawaddah and rahmah is the desire of everyone. The obsession to realize a harmonious family should be achieved in a earnest way. The principles underlying the formation of a harmonious family from a hadith's perspective include the way to choose an ideal partner in life, criteria for choosing a mate, the obligation of a husband to his wife, and the wife's duty to her husband. According to the Hadith, an ideal partner in life either husband or wife should be based on piety and obedience to God, and mutual understanding between both husband and wife.